2015
DOI: 10.1007/s10753-015-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Vicenin-2 and Scolymoside on TGFBIp-Induced Septic Responses

Abstract: Transforming growth factor β-induced protein (TGFBIp) is an extracellular matrix protein whose expression in several cell types is greatly increased by TGF-β. TGFBIp is released by the human umbilical vein endothelial cells (HUVECs) and functions as a mediator of experimental sepsis. Cyclopia subternata is a medicinal plant commonly used in traditional medicine to relieve pain in biological processes. In this study, we investigated the antiseptic effects and underlying mechanisms of vicenin-2 and scolymoside, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…ViceninII exhibits significant anticancer activities that inhibit the growth of prostate cancer (PC-3, DU-145 and LNCaP cells) in-vitro and in-vivo [51,52] and induce apoptosis in hT-29 human colon cancer cells [53]. In addition, many critical literatures has been reported that ViceninII has shown anti-inflammatory effect through the inhibition of TGF-β-induced protein signaling pathway as well as induced apoptosis of lung cancer H23 cell via PI3K/Akt/mTOR signaling [54,55]. However, none of the previous investigations investigated the anti-metastasis effects and its molecular mechanism of ViceninII in lung adenocarcinoma A549 and H1299 cells.…”
Section: Introductionmentioning
confidence: 99%
“…ViceninII exhibits significant anticancer activities that inhibit the growth of prostate cancer (PC-3, DU-145 and LNCaP cells) in-vitro and in-vivo [51,52] and induce apoptosis in hT-29 human colon cancer cells [53]. In addition, many critical literatures has been reported that ViceninII has shown anti-inflammatory effect through the inhibition of TGF-β-induced protein signaling pathway as well as induced apoptosis of lung cancer H23 cell via PI3K/Akt/mTOR signaling [54,55]. However, none of the previous investigations investigated the anti-metastasis effects and its molecular mechanism of ViceninII in lung adenocarcinoma A549 and H1299 cells.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, among the flavones tested, scolymoside (SCL) (26), vicenin‐2 (VCN) (29; Lee et al, 2015, 2020), and wogonin (WGN) (30) (Dai et al, 2021; Kwak et al, 2014) presented the most significant results of this class. These flavones increased both life expectancy and the survival rate of the animals with sepsis when compared with an untreated CLP group.…”
Section: Resultsmentioning
confidence: 99%
“…Rutin has attracted attention as a new antioxidant [77], and vicenin-2 has exhibited anticancer activity by inhibiting the growth of prostate cancer (DU-145, PC-3, and LNCaP cells) cells in vivo and in vitro [78,79] and by inducing apoptosis in HT-29 human colon cancer cells [80]. In addition, vicenin-2 has shown an anti-inflammatory effect by suppressing the protein signaling pathway triggered by TGFβ and inducing H23 cell death through PI3K/Akt/mTOR signaling [81,82]. Vicenin-2 is a major flavonoid component of D. caulis [78], and academic consensus suggests that flavonoids can cross the blood-brain barrier (BBB) and reach the central nervous system [83].…”
Section: Discussionmentioning
confidence: 99%